Evolving Strategies in the Detection and Management of Left Ventricular Thrombus: A Clinical Summary - Abdelnabi, Mahmoud; Ibrahim, Ramzi; Pham, Hoang Nhat; Saleh, Yehia; Almaghraby, Abdallah (Current Cardiology Reviews, 2025)
Recent advancements have emerged in understanding the epidemiology and optimal therapeutic options for left ventricular thrombi (LVT). With early percutaneous interventions in acute myocardial infarction, the prevalence of LVT has decreased. However, the best strategies for prevention, risk stratification, and management remain unclear, especially among non-ischemic cardiomyopathy disorders. This review outlines these advancements and provides an overview of the diagnostic and therapeutic implications of LVT in ischemic and non-ischemic cardiomyopathies. Significant gaps in the current evidence persist, particularly regarding the optimal timing for LVT screening and the need for prophylactic anticoagulation, highlighting opportunities for prospective cohort studies. Furthermore, a better understanding of the unique risk factors that contribute to increased LVT risk would lead to more comprehensive algorithms that may quantify the risk of LVT development, aiding in developing preventive strategies targeted at reducing rates of LVT. Until more definitive evidence is available, clinicians should custom LVT screening, preventive measures, and management strategies based on individual patient risk factors.
Keywords: thromboembolic events